Gingival overgrowth following mechanical trauma during tooth preparation: a case report - Sulastrianah Sulastrianah; Sri Oktawati (DiscoverSys Inc., 2019)
Objective: To explain the management of gingival overgrowth caused by mechanical trauma during tooth preparation.Method: In this case report, a patient experience gingival overgrowth one day after trauma during tooth preparation for bridge. The patient feel severe paint especially when the inflamed gingiva is bitten during occlusion. In intraoral examination overgrowth is localized red to pink white, firm nodule gingiva. Management of the patient is surgical removal of the overgrowth gingivaResults: After one week of operation, the gingiva shows a good healing and no recurrency.Conclusion: Gingival overgrowth may develop as a result from trauma or chronic irritation. The High speed rotary instrument may also make the trauma in the gingiva during tooth preparation. The carefully is needed when using this instrument.